Structural and spectroscopic studies of Au(III) chloride compounds with 7, 8-benzoquinoline. (8th January 2018) - Niedzielska, Daria; Pazderski, Leszek; Wojtczak, Andrzej; Kurzawa, Marzena; Ścianowski, Jacek; Szłyk, Edward
Graphical abstract: X-ray and 1 H, 13 C and 15 N NMR study of Au(III) chloride compounds with 7, 8-benzoquinoline. Abstract: Au(III) chloride compounds with 7, 8-benzoquinoline (bqn) – [Au(bqn)Cl3 ] and [Au(bqn ∗ )Cl2 ] (bqn ∗ being deprotonated, at the C(10) carbon, monoanionic form of bqn) were studied by 1 H– 13 C, 1 H– 15 N HMQC and HMBC–NMR. 1 H, 13 C and 15 N coordination shifts were discussed in relation to the molecular structures, revealing characteristic variability patterns. Analogous NMR measurements were performed for the new (bqnH + )2 (AuCl4 − )Cl − salt, studied also by single crystal X-ray diffraction. All compounds exhibited fluorescence.